2021
DOI: 10.1089/tmj.2021.0127
|View full text |Cite
|
Sign up to set email alerts
|

A Telehealth Initiative to Overcome Health Care Barriers for People Experiencing Homelessness

Abstract: People experiencing homelessness (PEH) encounter barriers to health care, increasing their vulnerability to illness, hospitalization, and death. Telehealth can improve access to health care, but its use in PEH has been insufficiently evaluated. Needs assessment surveys completed by clients at an urban drop-in center for PEH (n = 63) showed mental (58.7%) and physical (52.4%) health challenges were common, as was emergency department (ED) use (75.9%, n = 54). Surveys collected after in-person and telehealth cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Although not rigorously evaluated in the reviewed articles, other potential benefits of tele-OPAT include reduced frequencies of clinic visits and late/missed appointments, and reduction in health disparities. 9, [34][35][36] By reducing in-person visits and travel-related emissions, tele-OPAT also offer a potential opportunity to reduce the carbon footprints of healthcare systems, and thus helps in the fight against climate change. 37 One key knowledge gap within the reviewed literature relates to patient experience and provider acceptance/perspectives on tele-OPAT.…”
Section: Discussionmentioning
confidence: 99%
“…Although not rigorously evaluated in the reviewed articles, other potential benefits of tele-OPAT include reduced frequencies of clinic visits and late/missed appointments, and reduction in health disparities. 9, [34][35][36] By reducing in-person visits and travel-related emissions, tele-OPAT also offer a potential opportunity to reduce the carbon footprints of healthcare systems, and thus helps in the fight against climate change. 37 One key knowledge gap within the reviewed literature relates to patient experience and provider acceptance/perspectives on tele-OPAT.…”
Section: Discussionmentioning
confidence: 99%
“…Technology-based treatments for mental health including tele-therapy, text messages, and mobile apps have been promising in delivering treatment to various populations. The COVID-19 pandemic certainly increased the popularity of telehealth solutions, transforming the way people receive health care; however, many providers from all specialties were developing telehealth tools prior to the pandemic [ 6 8 ].…”
Section: Telehealth As a Proposed Solutionmentioning
confidence: 99%
“…In terms of success outcomes, telehealth modalities to improve access, specifically video visits, have been found to have high levels of satisfaction for both patients and providers [ 6 , 19 •, 21 ]. Recent research reveals technological interventions show high rates of clinical benefit, including reduction of symptoms of psychopathology, specifically for PTSD, depression, and anxiety [ 6 , 15 , 16 ].…”
Section: Telehealth As a Proposed Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study of telehealth found no differences in total outpatient visits after hospital discharge, early in the pandemic [ 8 ]. In a survey of people experiencing homelessness, 29.1% self-reported they would have sought care in an emergency department (ED) if they had not had access to telehealth [ 9 ]. Additional evidence on whether telehealth complements or substitutes for in-person care is lacking.…”
Section: Introductionmentioning
confidence: 99%